A composite sand powder material and its preparation method and application
By crushing, decomposing, magnetic separation, and washing and calcining the investment cast waste shell, sodium silicate is removed and calcium silicate is generated. Combined with dry ball milling and high-temperature smelting, composite sand powder material is prepared, which solves the problem of recycling and utilization of sodium silicate bonded waste shell, and achieves high refractory and mechanical strength of the material, which is suitable for a variety of applications.
Patent Information
- Application Number
- CN202411429482.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-10-14
AI Technical Summary
The prior art is difficult to effectively recycle and utilize investment casting waste shells bonded by sodium silicate generated during investment casting, resulting in waste of refractory materials and environmental pollution.
By crushing, removing impurity, and magnetic separation of the investment cast waste shell bonded with sodium silicate, mixing and washing and calcining it, removing sodium silicate residues and producing calcium silicate with good refractory properties. Then the mixed sand, magnesium oxide sand and boron nitride are subjected to dry ball milling and high temperature smelting to form a composite melt, and finally the composite sand powder material is obtained by compression and consolidation.
The effective removal of sodium silicate and the formation of calcium silicate are achieved, which significantly improves the refractory performance and mechanical strength of the material. It can be used to prepare cast sand, building materials and stone, and has the effects of waterproof, fireproof, corrosion-proof and wear-resistant.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of recycled foundry sand, and in particular to a composite sand powder material and a preparation method and application thereof. Background Art
[0002] The main components of investment casting waste shells include face sand, back sand, slurry, etc., which are all refractory materials. In the investment casting process, about 1.1 to 1.5 tons of waste shells are generated for every ton of castings produced. If these waste shells are directly discarded, it will not only cause a huge waste of refractory materials, but also pollute soil and water resources, causing serious harm to the environment.
[0003] In addition, a binder needs to be added during the mold casting process, and sodium silicate is the most commonly used one. Therefore, there will be a lot of sodium silicate residues in the waste casting sand, because sodium silicate will decompose and produce gas at 1100℃, which will affect the refractory performance and high temperature stability of the sand powder. The commonly used method to remove sodium silicate is pickling, but pickling will waste acid, because the acid will react with the metal oxides in the shell during the pickling process, and the generated salt substances are difficult to recycle, resulting in the loss of acid. Summary of the invention
[0004] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a composite sand powder material and a preparation method and application thereof.
[0005] To achieve the above object, the technical solution adopted by the present invention is:
[0006] In a first aspect, the present invention provides a method for preparing a composite sand powder material, comprising the following steps:
[0007] S1, crushing and removing impurities from the sodium silicate-bonded investment casting waste shell to obtain sodium silicate-bonded casting waste sand, then performing a shaking table powder sieve, and then performing magnetic separation to remove iron filings in the waste sand;
[0008] S2, mixing the foundry waste sand and the waste gypsum, then washing and drying at 70-90° C., and calcining at 1200-1300° C. after washing to obtain mixed sand, wherein the mass ratio of the foundry waste sand to the waste gypsum is 1:(0.3-0.5);
[0009] S3, mixing the mixed sand, magnesia sand and boron nitride and performing dry ball milling to obtain a mixture, adding a flux, and then smelting at 1500-2000° C. to obtain a composite melt; wherein the mass ratio of the mixed sand, magnesia sand and boron nitride is (50-60): (10-20): (1-5);
[0010] S4, the composite melt is cooled to obtain an ingot; the ingot is chipped and crushed to obtain composite sand powder, and then the composite sand powder is compressed and consolidated in a mold, and then crushed after being taken out to obtain the composite sand powder material.
[0011] The main refractory components of foundry waste sand are alumina, silicon dioxide and zirconium oxide, all of which have good refractoriness and chemical stability. The main component of waste gypsum is calcium sulfate, and its content is generally above 80%. In the washing step of step S2, calcium sulfate and sodium silicate in foundry waste sand generate water-insoluble calcium silicate (CaSiO3) precipitation: CaSO4+Na2SiO3→CaSiO3+Na2SO4.
[0012] Calcium silicate has high hardness and wear resistance, which can significantly improve the mechanical strength of the material. At the same time, calcium silicate is also a high-performance refractory material. Its non-combustible properties meet the national A1 fire rating standard, which can significantly improve the fire resistance of the material.
[0013] After washing, the foundry waste sand needs to be calcined at 1200-1300℃. At this temperature, calcium sulfate will undergo the following three reactions:
[0014] 1. Calcium sulfate decomposes to form calcium oxide: 2CaSO4→2CaO+2SO2↑+O2↑;
[0015] 2. Calcium sulfate can react with silicon dioxide: 2CaSO4+2SiO2→2CaSiO3+2SO2↑+O2↑;
[0016] 3. Calcium oxide reacts with silicon dioxide: CaO+SiO2→CaSiO3.
[0017] Since the first two reactions will generate gas, pores or cracks will be formed in the sand powder, increasing the porosity of the sand powder. The increase in porosity will reduce the strength and density of the sand powder, and affect its physical properties such as water absorption and air permeability. In order to avoid the above effects, secondary smelting is required to improve the density of the product. CaSiO3 has a high melting point and can form a stable glass phase at high temperatures, which helps to improve the refractoriness of the sand powder and reduce the problem of sand mold collapse during high-temperature pouring. Moreover, CaSiO3 can react with water to form hydrated calcium silicate. By forming a waterproof layer, it can reduce the erosion of water on the sand mold and extend the service life of the sand mold, thereby improving the waterproof performance of the sand powder.
[0018] The mixed sand, magnesium oxide sand and boron nitride are compounded by ball milling. Boron nitride has high thermal conductivity and electrical insulation. After dry ball milling, it is melted. In a high-temperature melting environment of 1500-2000°C, magnesium oxide (MgO) and aluminum oxide (Al2O3) contained in the mixed sand generate magnesium aluminum spinel (MgAl2O4), which has a high melting point and can significantly improve the refractory temperature of the aggregate. Under high temperature environment, magnesium aluminum spinel can maintain stable chemical and physical properties, thereby extending the service life of the aggregate. It can also significantly increase the hardness of the aggregate, making it more wear-resistant. When subjected to friction or impact, aggregates with magnesium aluminum spinel components can better resist wear and maintain their integrity. Magnesium aluminum spinel, as a binding phase between grains, can improve the microstructure of the material, enhance its density, and further improve its wear resistance.
[0019] Ball milling these materials can form a composite material with synergistic effects, thereby improving the comprehensive performance of the final material. Moreover, ball milling promotes the interface bonding between different materials and reduces the interface porosity, thereby improving the fire resistance and mechanical strength of the material.
[0020] The composite sand powder is then compressed and consolidated in a mold before being crushed. Due to the compression enhancement, the uniformity of the distribution of particles on the matrix is improved, the structure of the matrix material is refined, and the volume porosity during hot pressing is reduced. Tests have shown that it can significantly improve the mechanical properties of the material.
[0021] Preferably, in step S1, the rotation speed of magnetic separation is 10-20 r / min, and the magnetic induction intensity is 150-200 mT.
[0022] Preferably, the water washing treatment includes two water washing and drying steps, and the solid-liquid ratio of the first water washing is 1:2; the solid-liquid ratio of the second water washing is 1:3. Because calcium hydroxide and sodium silicate generate calcium silicate through hydrothermal reaction, in order to make the reaction complete and remove the impurities of the generated sodium hydroxide, two water washing and drying are arranged.
[0023] Preferably, in step S2, the washing is performed with stirring at a speed of 200 to 800 r / min; the drying temperature is 100 to 110° C., and the drying time is 1 to 2 h.
[0024] Preferably, the ball-to-material ratio in the ball milling in step S3 is (5-10):1, the rotation speed of the ball milling is 50-70 r / min, and the time is 30-60 min.
[0025] Preferably, in step S3, the smelting time is 6 to 8 hours, and the amount of flux added is 0.1 to 0.5 wt% of the mass of the mixture.
[0026] Preferably, the flux comprises the following components in parts by weight: 45-50 parts of potassium chloride, 25-30 parts of sodium chloride and 20-25 parts of sodium hexafluoroaluminate. During the smelting process, the flux forms a continuous and complete covering layer on the surface of the metal oxide melt by the effect of surface tension, effectively isolating the air and preventing the melt from reacting with oxygen, water vapor, etc. at high temperature, resulting in oxidation or combustion.
[0027] Preferably, in step S4, the compression consolidation molding is performed at a pressure of 300-350 MPa, a temperature of 400-500° C., and a time of 20-30 min.
[0028] In a second aspect, the present invention provides a composite sand powder material prepared by the above-mentioned method for preparing the composite sand powder material.
[0029] In a third aspect, the present invention provides an application of composite sand powder material for preparing foundry sand, building materials and stone materials. The building materials are aggregates of concrete; preparing stone materials refers to mixing the materials with adhesives and other ingredients, spraying them on the surface of the stone materials to increase the wear resistance, thereby obtaining stone materials with better wear resistance.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] The present invention recycles the refractory material in the waste shell of investment casting bonded with sodium silicate. Specifically, sodium silicate is bonded with waste casting sand and waste gypsum, and the sodium silicate in the waste casting sand reacts hydrothermally with the calcium sulfate in the waste gypsum. While removing the sodium silicate, calcium silicate with good refractory performance is also generated. Then, after high-temperature calcination, calcium sulfate can react with silicon dioxide to generate calcium silicate, and calcium sulfate is decomposed into calcium oxide. Calcium oxide reacts with silicon dioxide in the waste casting sand to generate calcium silicate, thereby obtaining mixed sand. Subsequently, the mixed sand is compounded with magnesium oxide sand and boron nitride through dry ball milling, and then smelted at high temperature. At the same time, magnesium oxide reacts with aluminum oxide in the waste casting sand to generate magnesium aluminum spinel (MgAl2O4), thereby further improving the refractory and mechanical properties of the material. After the composite melt is formed, it is crushed to obtain composite sand powder, and the composite sand powder is compressed and consolidated in a mold. The compression can effectively improve the uniformity of the distribution of particles on the matrix, so that the structure of the matrix material is refined, thereby further improving the mechanical strength of the material. The material prepared as above has good fire resistance and mechanical strength, and can be used to prepare foundry sand, building materials and stone materials, giving the final product waterproof, fireproof, corrosion-resistant and wear-resistant effects. DETAILED DESCRIPTION
[0032] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0033] In the following examples and comparative examples, the sources of the reagents used are as follows:
[0034] Sodium silicate bonded investment casting waste shell: from Jiangmen Guangjin Casting and Forging Co., Ltd.;
[0035] Waste gypsum: from Dehua County Huanyi Recycling Resources Co., Ltd.;
[0036] Magnesia sand: the manufacturer is Yancheng Huanai Magnesium Industry Co., Ltd., the particle size is 1-3mm, the composition is MgO ≥ 97wt%, CaO ≤ 1.4wt%, SiO2 ≤ 0.7wt%;
[0037] Boron nitride: The manufacturer is Henan Boron Nitride New Material Technology Co., Ltd., the brand is PBN500;
[0038] Zircon quartz sand: manufacturer is Shandong Golden Sun Zirconium Co., Ltd., 80-100 mesh;
[0039] Silica sol: The manufacturer is Shandong Zengfu Industry and Trade Co., Ltd., the brand is Excellence 004;
[0040] Mullite powder: manufacturer is Shandong Chenyuan Powder Co., Ltd., 200 mesh;
[0041] Mullite sand: manufacturer is Shandong Chenyuan Powder Co., Ltd., 80-120 mesh;
[0042] Portland cement: the manufacturer is China Resources Cement (Shantou) Co., Ltd., the brand is P.O42.5R ordinary;
[0043] Latex powder: The manufacturer is Wacker Chemical Company of Germany, the brand is 5010N;
[0044] Hydroxypropyl methylcellulose: The manufacturer is Hebei Haoshuo Chemical Co., Ltd., the model is 9900-75,000 viscosity, original Chinese packaging;
[0045] Unless otherwise specified, other materials, reagents, etc. used in the examples and comparative examples can be obtained from commercial sources.
[0046] Example 1
[0047] A method for preparing a composite sand powder material comprises the following steps:
[0048] S1. The waste shell of investment casting bonded with sodium silicate is crushed and impurities are removed to obtain the waste sand bonded with sodium silicate, which is then screened by a shaking table, and then magnetically separated to remove iron filings in the waste sand; the speed of the magnetic separation is 15r / min, and the magnetic induction intensity is 180mT;
[0049] S2. Mix the foundry waste sand and waste gypsum, then wash and dry them at 85°C and at a speed of 600r / min while stirring, and calcine them after washing to obtain mixed sand; the mass ratio of the foundry waste sand to the waste gypsum is 1:0.45; the washing treatment includes secondary washing and drying steps, the solid-liquid ratio of the first washing is 1:2; the solid-liquid ratio of the second washing is 1:3; the calcination temperature is 1350°C, the time is 1.5h, and the drying temperature is 105°C, and the time is 1.5h.
[0050] S3, dry ball milling the mixed sand, magnesium oxide sand and boron nitride to obtain a mixture, then adding a flux and smelting at 1800°C for 7 hours to obtain a composite melt; wherein the mass ratio of the mixed sand, magnesium oxide sand and boron nitride is 55:12:3; the ball-to-material ratio in the ball milling is 7:1, the speed of the ball milling is 60r / min, and the time is 50min. The amount of the flux added is 0.3wt% of the mass of the mixture. The flux includes the following components in parts by weight: 48 parts of potassium chloride, 26 parts of sodium chloride and 22 parts of sodium hexafluoroaluminate.
[0051] S4, the composite melt is cooled to obtain an ingot; the ingot is chipped and crushed to obtain composite sand powder, and then the composite sand powder is compressed and consolidated in a mold at a pressure of 320 MPa and a temperature of 450° C. for 25 minutes, and then crushed after being taken out to obtain the composite sand powder material.
[0052] Example 2
[0053] A method for preparing a composite sand powder material comprises the following steps:
[0054] S1. The waste shell of investment casting bonded with sodium silicate is crushed and impurities are removed to obtain the waste sand bonded with sodium silicate, and then the waste sand is screened by a shaking table, and then the iron filings in the waste sand are removed by magnetic separation; the rotation speed of the magnetic separation is 10r / min, and the magnetic induction intensity is 150mT;
[0055] S2. Mix the foundry waste sand and waste gypsum, then wash and dry them at 70°C and at a speed of 200r / min while stirring, and calcine them after washing to obtain mixed sand; the mass ratio of the foundry waste sand to the waste gypsum is 1:20; the washing treatment includes secondary washing and drying steps, the solid-liquid ratio of the first washing is 1:2; the solid-liquid ratio of the second washing is 1:3; the calcination temperature is 1300°C, the time is 2h, and the drying temperature is 100°C, and the time is 2h.
[0056] S3, dry ball milling the mixed sand, magnesium oxide sand and boron nitride to obtain a mixed material, then adding a flux and smelting at 1500°C for 8 hours to obtain a composite melt; wherein the mass ratio of the mixed sand, magnesium oxide sand and boron nitride is 50:10:1; the ball-to-material ratio in the ball milling is 5:1, the speed of the ball milling is 50r / min, and the time is 60min. The amount of the flux added is 0.1wt% of the mass of the mixed material. The flux includes the following components in parts by weight: 50 parts of potassium chloride, 30 parts of sodium chloride and 25 parts of sodium hexafluoroaluminate.
[0057] S4, the composite melt is cooled to obtain an ingot; the ingot is chipped and crushed to obtain composite sand powder, and then the composite sand powder is compressed and consolidated in a mold at a pressure of 300 MPa and a temperature of 400° C. for 30 minutes, and then crushed after being taken out to obtain the composite sand powder material.
[0058] Example 3
[0059] A method for preparing a composite sand powder material comprises the following steps:
[0060] S1. The waste shell of investment casting bonded with sodium silicate is crushed and impurities are removed to obtain the waste sand bonded with sodium silicate, and then the waste sand is screened by a shaking table, and then the iron filings in the waste sand are removed by magnetic separation; the rotation speed of the magnetic separation is 20r / min, and the magnetic induction intensity is 200mT;
[0061] S2. Mix the foundry waste sand and waste gypsum, then wash and dry them at 90°C and at a speed of 800r / min while stirring, and calcine them after washing to obtain mixed sand; the mass ratio of the foundry waste sand to the waste gypsum is 1:30; the washing treatment includes secondary washing and drying steps, the solid-liquid ratio of the first washing is 1:2; the solid-liquid ratio of the second washing is 1:3; the calcination temperature is 1400°C, the time is 1h, and the drying temperature is 110°C, and the time is 1h.
[0062] S3, dry ball milling the mixed sand, magnesia sand and boron nitride to obtain a mixed material, then adding a flux and smelting at 2000°C 6 to obtain a composite melt; wherein the mass ratio of the mixed sand, magnesia sand and boron nitride is 60:20:5; the ball-to-material ratio in the ball milling is 10:1, the speed of the ball milling is 70r / min, and the time is 30min. The amount of the flux added is 0.5wt% of the mass of the mixed material. The flux includes the following components in parts by weight: 45 parts of potassium chloride, 25 parts of sodium chloride and 20 parts of sodium hexafluoroaluminate.
[0063] S4, the composite melt is cooled to obtain an ingot; the ingot is chipped and crushed to obtain composite sand powder, and then the composite sand powder is compressed and consolidated in a mold at a pressure of 350 MPa and a temperature of 500° C. for 20 minutes, and then crushed after being taken out to obtain the composite sand powder material.
[0064] Example 4
[0065] The difference between Example 4 and Example 1 is that in step S2 of Example 4, only one water washing is performed.
[0066] Embodiment 5-8
[0067] The difference between Example 5-8 and Example 1 is that: in the step S2, stirring is performed during the water washing, and the stirring speed is 200r / min, 400r / min and 800r / min respectively.
[0068] Comparative Example 1
[0069] The difference between Comparative Example 1 and Example 1 is that the foundry waste sand in Comparative Example 1 is not subjected to the steps of adding waste gypsum for washing and calcining at 1350° C. in step S2 .
[0070] Comparative Example 2
[0071] The difference between Comparative Example 2 and Example 1 is that in Comparative Example 2, instead of adding waste gypsum for water washing and calcining at 1350° C. in step S2, a hydrofluoric acid solution with a mass concentration of 10% is added to acid-wash the waste foundry sand.
[0072] Comparative Example 3
[0073] The difference between Comparative Example 3 and Example 1 is that the melting temperature of step S3 of Comparative Example 3 is 1450°C.
[0074] Comparative Example 4
[0075] The difference between Comparative Example 4 and Example 1 is that the melting temperature of step S3 of Comparative Example 4 is 2050°C.
[0076] Comparative Example 5
[0077] The difference between Comparative Example 5 and Example 1 is that no magnesia sand is added to the material of Comparative Example 5.
[0078] Comparative Example 6
[0079] The difference between Comparative Example 6 and Example 1 is that no boron nitride is added to the material of Comparative Example 6.
[0080] Comparative Example 7
[0081] The difference between Comparative Example 7 and Example 1 is that the material of Comparative Example 7 is not subjected to compression consolidation molding.
[0082] Comparative Example 8
[0083] The difference between Comparative Example 8 and Example 1 is that no flux is added during the smelting process of Comparative Example 8.
[0084] Comparative Example 9
[0085] The difference between Comparative Example 9 and Example 1 is that in step S2 of Comparative Example 9, high-temperature calcination at 1350° C. is not performed after washing.
[0086] Comparative Example 10
[0087] The difference between Comparative Example 10 and Example 1 is that magnesium oxide sand and boron nitride are not added to the material of Comparative Example 10.
[0088] Specific application 1
[0089] The sand powder materials of Examples 1 to 8 and Comparative Examples 1 to 10 are respectively used as surface sand powder to make shell specimens. The preparation method of the shell is: first, a wax mold needs to be made by pressing, and then it is coated and sanded. When coating, the wax mold should be immersed in the coating for 20 seconds, and repeated three times. After each layer of shell coating is completed, it needs to be dried at room temperature for a certain time before the next layer of shell coating is carried out. After all the coatings are dried, the shell is placed in a furnace at room temperature, and the baking furnace is set to a heating rate of 5°C / min, the baking temperature is 900°C, and after keeping warm for 120 minutes, it is cooled to room temperature with the furnace. Among them, the raw material of the wax mold is SL162 wax. The refractory powder and proportion selected for the surface layer, transition layer and back layer are shown in Table 1.
[0090] Table 1 Composition of refractory powder of each layer of shell
[0091]
[0092] Test Method
[0093] (1) Shell bending strength
[0094] The shell specimen size for testing the bending strength of the shell is a 40mm×20mm×6mm square specimen. The strength test adopts the three-point bending method and is carried out according to the "Aviation Industry Standard of the People's Republic of China HB5352.1-2004". The bending strength of the shell specimen is calculated according to formula (1):
[0095]
[0096] Wherein, σw is the bending strength, MPa; P is the load when the sample breaks, N; L is the span between the two supports, mm; a is the width of the sample, mm; h is the thickness of the sample, mm. Specific data are shown in Table 2. The room temperature bending strength of the shell was tested before firing, that is, after being placed at room temperature for 2 hours, after demolding, the firing bending strength of the shell was tested after firing at 900℃, and then the high temperature bending strength of the shell was tested after firing at 1300℃ for 120min.
[0097] (2) High temperature self-weight deformation of the shell
[0098] The high-temperature self-weight deformation specimen is a circular specimen with an outer diameter of 100 mm, an inner diameter of 88 mm, and a depth of 6 mm. The high-temperature self-weight deformation test of the mold shell is based on the "People's Republic of China Aviation Industry Standard HB5352.2-2004 Investment Casting Shell Performance Test Method-Part 2: Determination of High-temperature Self-weight Deformation". After being kept at 1200℃ for 2 hours, the high-temperature self-weight deformation rate of the specimen is calculated according to formula (2).
[0099] (2);
[0100] Where, δt−τ is the high-temperature self-weight deformation of the sample, %; A is the original outer diameter of the sample, mm; B is the outer diameter of the sample after deformation, mm. The size of the high-temperature load deformation sample of the shell is 88 mm×20 mm×(6±0.5) mm. After placement, the temperature is raised to 1200°C, and a load of 3 N is applied to the sample. After keeping warm for 1h, it is cooled to room temperature with the furnace, and the sample is taken out to measure the deformation H. Specific data are shown in Table 2.
[0101] Table 2 Data of each group of shell specimens
[0102]
[0103]
[0104] As shown in Table 1, the bending strength of each group after firing is significantly improved compared with the strength at room temperature. This is because after firing, the shell loses almost all hydroxyl water, and some hydroxyl groups are converted into silicon oxygen bonds, so the shell strength will be higher. In addition, the structure of the shell becomes denser, and a better connection is formed between the coating and the sanding material. The shell obtained from the sand powder material of Example 1 has good mechanical properties and the best heat resistance.
[0105] The shell performance of Example 4 is lower than that of Example 1. Since calcium sulfate and sodium silicate generate calcium silicate through a hydrothermal reaction, secondary water washing and drying can complete the reaction and completely remove the generated sodium sulfate impurities, thereby improving the performance of the sand powder material.
[0106] Example 1 and Example 5-8 respectively explore the effect of stirring rate on performance during the water washing process. According to the data, the preferred stirring rate is 600r / min, and the change in stirring speed will affect the particle size, moisture content and bulk density of the calcium silicate particles. As the stirring speed increases, the particle size of the calcium silicate particles gradually becomes smaller. This is because a higher stirring speed can enhance the collision and shear force between the particles, thereby promoting the refinement of the particles. The bulk density shows a trend of gradual increase, indicating that the compactness of the particles is improved, which helps to improve the overall performance of the material. Although the increase in stirring speed helps to refine the particles, when the stirring rate exceeds 600r / min, the yield of porous calcium silicate decreases. This shows that in the hydrothermal synthesis process, the stirring speed needs to be moderately controlled to achieve the best yield and particle characteristics.
[0107] In Comparative Example 1, no waste gypsum was added, and sodium silicate still existed in the sand powder. After being calcined at 1300°C, its flexural strength was significantly reduced. This is because sodium silicate decomposes at 1100°C to produce gas, which will affect the refractory performance and high-temperature stability of the sand powder. This shows that calcium sulfate in waste gypsum can react chemically with sodium silicate to generate water-insoluble calcium silicate (CaSiO3) precipitation, thereby removing sodium silicate residues.
[0108] Comparative Example 2 uses common pickling to remove sodium silicate from the waste shell of investment casting, but also does not add waste gypsum. It is the same as Comparative Example 1, and the mechanical strength and fire-resistant and heat-resistant properties are significantly reduced. This is because the calcium oxide generated by the high-temperature decomposition of waste gypsum can react chemically with sodium silicate to generate water-insoluble calcium silicate (CaSiO3) precipitation. Calcium silicate has high hardness and wear resistance, which can significantly improve the mechanical strength of the material. At the same time, calcium silicate is also a high-performance refractory material, and its non-combustible performance meets the national A1 fire rating standard, thereby significantly improving the fire resistance of the material. At the same time, it can be seen from the high-temperature flexural strength data that because calcium silicate itself is a heat-resistant material, it can still play a certain reinforcing role in the shell after high temperature.
[0109] The melting temperatures of Comparative Examples 3 and 4 are not within the range of 1500-2000°C. The melting temperature of Comparative Example 3 is too low, and the chemical composition in the melt is uneven, resulting in uneven material properties, thereby affecting the fire resistance and mechanical strength of the material. The melting temperature of Comparative Example 4 is too high, and the material grains grow excessively, affecting the microstructure and mechanical properties of the material, thereby affecting the dimensional stability and machining performance.
[0110] In Comparative Example 5, no magnesia sand is added, and its mechanical strength and high temperature stability are also significantly reduced. This is because magnesium oxide (MgO) and aluminum oxide (Al2O3) contained in the mixed sand generate magnesium aluminum spinel (MgAl2O4), which has a higher melting point and can significantly increase the refractory temperature of the aggregate. Under high temperature environment, magnesium aluminum spinel can maintain stable chemical and physical properties, thereby extending the service life of the aggregate. It can also significantly increase the hardness of the aggregate, making it more wear-resistant.
[0111] In Comparative Example 6, no boron nitride is added, and the performance of the product is also significantly reduced. This is because boron nitride has a high melting point and good high temperature resistance, and the composite material can maintain stable structure and performance under high temperature environment. In addition, boron nitride has a low thermal expansion coefficient. After being compounded with mixed sand and magnesia sand, the thermal expansion coefficient of the material can be reduced, thereby improving the thermal stability requirements of the product.
[0112] The product of Comparative Example 7 is not compressed, and the mechanical strength of its shell decreases. This is because the sand powder material is strengthened after compression, the uniformity of particle distribution on the matrix is improved, the structure of the matrix material is refined, and the volume porosity during hot pressing is reduced, so it can significantly improve the mechanical properties of the material.
[0113] In Comparative Example 8, no flux is added during the smelting process, and its mechanical strength and high-temperature stability are also significantly reduced, indicating that during the smelting process, the flux forms a continuous and complete covering layer on the surface of the metal oxide melt with the help of surface tension, effectively isolating the air and preventing the melt from reacting with oxygen, water vapor, etc. at high temperature, leading to oxidation or combustion.
[0114] In step S2 of comparative example 9, high-temperature calcination is not performed after washing, so the calcium sulfate in the waste gypsum is not decomposed into calcium oxide, that is, the calcium sulfate is retained in the mixed sand, and then in step S3, the calcium sulfate reacts with silicon dioxide to generate gases such as calcium sulfate, sulfur dioxide and oxygen, forming pores or cracks in the sand powder, increasing the porosity of the sand powder, and causing the product performance to decrease. To avoid this situation, the present invention places the reaction that generates gas in the first calcination, and then undergoes a second smelting without generating gas, thereby improving the density of the material.
[0115] In Comparative Example 10, no boron nitride and magnesium oxide are added. Compared with Comparative Examples 5 and 6, it is shown that boron nitride, magnesium oxide sand and foundry waste sand have a synergistic effect and can provide good refractory and mechanical properties for the mold shell.
[0116] Specific application 2
[0117] The sand powder materials of Examples 1 to 9 and Comparative Examples 1 to 10 were used as surface sand powder to prepare cement mortar samples. The specific formula of the cement mortar was: 50 parts of silicate cement, 4 parts of latex powder, 40 parts of sand powder materials of each group, 0.2 parts of hydroxypropyl methylcellulose, 0.2 parts of defoamer, 0.2 parts of water reducing agent, and 15 parts of polyvinyl alcohol aqueous solution with a mass concentration of 0.03%. Then the above ingredients were stirred at a speed of 500 rpm for 2 hours at room temperature to obtain cement mortar of each group.
[0118] Test Method
[0119] (1) Compressive strength and water absorption
[0120] The mortars of each group were poured into the test molds that meet the requirements of GB / T 17671 to make specimens, and then the compressive strength and water absorption parameters were measured according to the standard of JC / T 984-2011 "Polymer Cement Waterproof Mortar". See Table 3 for details.
[0121] (2) Corrosion resistance
[0122] The samples of each group were immersed in a sodium sulfate aqueous solution with a mass concentration of 5% for 7 days, and then taken out to measure the compressive strength according to the above method, and the loss rate (%) was calculated. See Table 3 for details.
[0123] Table 3 Data of each group of samples
[0124]
[0125]
[0126] As shown in Table 2, the cement mortar prepared from the sand powder material obtained in Example 1 has good mechanical strength, corrosion resistance and waterproof effects.
[0127] Example 1 and Examples 5-8 respectively explore the effect of stirring rate on performance during water washing. According to the data, the preferred stirring rate is 600r / min. It is known that changes in stirring speed will affect the particle size, moisture content, and bulk density of calcium silicate particles. The higher the particle characteristic compactness, the lower the water absorption rate of the product, thereby improving the waterproofness of the product.
[0128] No waste gypsum is added in Comparative Example 1, while in Comparative Example 2, sodium silicate in the waste shell of investment casting is removed by common pickling, but no waste gypsum is added. The waterproof and corrosion resistance of cement mortar are significantly reduced, because the calcium hydroxide in the waste gypsum can react chemically with the sodium silicate to generate water-insoluble calcium silicate (CaSiO3) precipitation. At the same time, the calcium hydroxide in the waste gypsum can also generate sodium silicate with the silicon dioxide in the waste casting sand. After high-temperature curing, the silicon and calcium in the calcium silicate will generate mineral phases such as tobermorite, which further enhances the density and durability of the cement mortar. At the same time, calcium silicate materials usually have good corrosion resistance and can resist the erosion of various chemical substances. After high-temperature smelting, calcium hydroxide decomposes into calcium oxide and water under high temperature conditions. Calcium oxide (CaO) has high stability at high temperatures and its melting point is extremely high, so as to further improve the waterproof, corrosion-resistant and mechanical properties of the material. Moreover, calcium oxide can also promote the sintering process of aggregate, making the aggregate particles more tightly bonded, thereby improving the overall waterproof performance.
[0129] In Comparative Example 5, no magnesium oxide sand is added, and its mechanical strength, waterproof and corrosion resistance are also significantly reduced. This is because magnesium oxide (MgO) and aluminum oxide (Al2O3) contained in the mixed sand generate magnesium aluminum spinel (MgAl2O4), which has excellent corrosion resistance and can remain stable in high temperature and chemical corrosion environments. At the same time, the high density and stable chemical properties of magnesium aluminum spinel help reduce the penetration of water, thereby improving the waterproof performance of the composite material.
[0130] In Comparative Example 6, no boron nitride is added, and the performance of the product is also significantly reduced. This is because boron nitride has high chemical stability and low surface energy, which makes the surface of the composite material have better water resistance. Moreover, it exhibits good anti-corrosion performance after being compounded with other components. The addition of boron nitride can reduce the micropores and cracks inside the coating cement mortar, thereby improving the corrosion resistance of the product.
[0131] The porosity of the sand powder material in the product of Comparative Example 7 is increased without compression, so the mechanical strength, waterproofness and corrosion resistance of the cement mortar are reduced. This shows that the sand powder material is strengthened by compression, the uniformity of the distribution of particles on the matrix is improved, the structure of the matrix material is refined, and the volume porosity during hot pressing is reduced, so it can significantly improve the mechanical properties of the material.
[0132] In comparative example 8, no flux is added during the smelting process, which will affect the performance of cement mortar. This is because during the smelting process, the flux forms a continuous and complete covering layer on the surface of the metal oxide melt by the effect of surface tension, effectively isolating the air and preventing the melt from reacting with oxygen, water vapor, etc. at high temperature, resulting in oxidation or combustion.
[0133] In step S2 of comparative example 9, high-temperature calcination is not performed after washing because the second smelting will cause calcium sulfate and silicon dioxide to react to generate gas, which will increase the porosity of the final sand powder, thereby affecting the mechanical strength, waterproofness and corrosion resistance of the cement mortar.
[0134] Boron nitride and magnesia sand are not added to the material of Comparative Example 10, and its performance is worse than that of Comparative Examples 5 and 6, indicating that boron nitride, magnesia sand and foundry waste sand have a synergistic effect and can provide good waterproof, corrosion-resistant and mechanical properties for cement mortar.
[0135] In summary, the material prepared as above has good fire resistance and mechanical strength, and can be used to prepare foundry sand, building materials and stone materials, giving the final product waterproof, fireproof, corrosion-resistant and wear-resistant effects.
[0136] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a composite sand powder material, characterized in that: The following steps are involved: S1, crushing and removing impurities from the sodium silicate-bonded investment casting waste shell to obtain sodium silicate-bonded casting waste sand, then performing a shaking table powder sieve, and then performing magnetic separation to remove iron filings in the waste sand; S2, mixing the foundry waste sand and the waste gypsum, then washing and drying at 70-90° C., and calcining after washing to obtain mixed sand, wherein the mass ratio of the foundry waste sand to the waste gypsum is 1:(0.3-0.5); S3, mixing the mixed sand, magnesia sand and boron nitride and performing dry ball milling to obtain a mixture, adding a flux, and then smelting at 1500-2000° C. to obtain a composite melt, wherein the mass ratio of the mixed sand, magnesia sand and boron nitride is (50-60): (10-20): (1-5); S4, the composite melt is cooled to obtain an ingot; the ingot is chipped and crushed to obtain composite sand powder, and then the composite sand powder is compressed and consolidated in a mold, and then crushed after being taken out to obtain the composite sand powder material.
2. The method for preparing the composite sand powder material according to claim 1, characterized in that: In the step S1, the rotation speed of magnetic separation is 10-20 r / min, and the magnetic induction intensity is 150-200 mT.
3. The method for preparing the composite sand powder material according to claim 1, characterized in that: The water washing treatment is a double water washing, the solid-liquid ratio of the first water washing is 1:2; the solid-liquid ratio of the second water washing is 1:
3.
4. The method for preparing the composite sand powder material according to claim 1 or 2, characterized in that: In the step S2, the washing is performed with stirring at a speed of 200 to 800 r / min; the drying temperature is 100 to 110° C. and the drying time is 1 to 2 h.
5. The method for preparing the composite sand powder material according to claim 1, characterized in that: The ball-to-material ratio in the ball milling in step S3 is (5-10):1, the rotation speed of the ball milling is 50-70 r / min, and the time is 30-60 min.
6. The method for preparing the composite sand powder material according to claim 1, characterized in that: In the step S3, the smelting time is 6 to 8 hours, and the amount of the flux added is 0.1 to 0.5 wt % of the mass of the mixture.
7. The method for preparing the composite sand powder material according to claim 6, characterized in that: The flux comprises the following components in parts by weight: 45-50 parts of potassium chloride, 25-30 parts of sodium chloride and 20-25 parts of sodium hexafluoroaluminate.
8. The method for preparing the composite sand powder material according to claim 1, characterized in that: In step S4, the compression consolidation molding is performed at a pressure of 300 to 350 MPa, a temperature of 400 to 500° C., and a time of 20 to 30 min.
9. A composite sand powder material, characterized in that: The composite sand powder material is prepared by the preparation method of the composite sand powder material according to any one of claims 1 to 8.
10. The composite sand powder material according to claim 9 is used for preparing foundry sand, building materials and stone materials.
Citation Information
Patent Citations
Chemical regeneration method in casting waste sand disposing process
CN102000764A
Refractory material prepared from investment casting waste sand and preparation method of refractory material
CN110156481A